METHODS OF TEACHING GYMNASTICS ACTIVITIES TO PRESCHOOL CHILDREN - Mirzаlimоv Muslimbek Soatjon о‘g‘li (Journals Park Publishing, 2025)
This article discusses the process of teaching gymnastics exercises to the younger generation, the effective methods and pedagogical approaches used in training, as well as the importance of such activities in promoting a healthy lifestyle. The impact of sports gymnastics on children's physical development is also highlighted.
Keywords: Physical education, exercise, sport, gymnastics, teaching methods, healthy lifestyle, J. Dims, sports gymnastics, pedagogical approaches.